(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
There are possibilities of potential hazards, as intravenous medications get rapid access to patients circulatory system. Calculating and applying drugs as per order of physician is complex because there are so many factors have to be taken into account. Regardless of the drug to be administered, careful and accurate calculations are important to avoid medication errors. Practicing drug calculation as per equations described in this article will minimize errors and maximize confidence among healthcare professionals. Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014